Butyric acid glycerides in the diet of broilers to replace conventional growth promoters: effects on performance, metabolism, and intestinal health - Ficagna C.A.* (2022)
© 2023 Informa UK Limited, trading as Taylor & Francis Group.This study aimed to determine whether butyric acid glycerides can replace conventional growth promoters, favour intestinal health, and improve performance. A total of 420 birds were used, divided into four groups with seven repetitions per group (n = 15), as follows: NC, negative control (no promoter); PC, positive control (basal diet + enramycin + salinomycin); MDT-BUT, a diet supplemented with mono-, di-, and triglycerides of butyric acid; TRI-BUT, a diet supplemented with tributyrin of butyric acid glycerides. Productive performance was measured on days 1, 21, 35, and 42. Excreta were collected for counting Escherichia coli and coliforms on days 21 and 42. Blood samples were collected at 42 days of age to analyse oxidant/antioxidant status, and the intestine was removed for intestinal morphometry. From 1 to 42 days, there was greater body weight, weight gain, and feed conversion in the PC, MDT-BUT, and TRI-BUT groups than in the NC group; the production efficiency index was 21.10% higher in all groups than in the NC group (p = 0.001). At 21 days, there were lower E. coli counts of 86.8% in the TRI-BUT and 99.7% in PC groups than in the NC and MDT-BUT groups (p < 0.001), while at 42 days, lower counts were found in the PC, MDT-BUT, and TRI-BUT groups than the NC group (p < 0.001). There were lower total protein and globulin levels in the MDT-BUT and TRI-BUT groups than in the NC group (p = 0.001). Cholesterol levels were lower in the TRI-BUT group, followed by MDT-BUT and PC groups, than in the NC group (p = 0.001), while lower triglyceride levels were found in the TRI-BUT group than in the NC and PC groups (p = 0.001). There were lower levels of lipid peroxidation and reactive oxygen species in the TRI-BUT group, followed by the PC group than the NC group (p < 0.001); on the other hand, there were higher protein thiol levels in the TRI-BUT group than the NC group (p = 0.041). The villus:crypt ratio increase was 79.4% in the TRI-BUT group, followed by the 45.1% PC and 19.8% MDT-BUT groups than the NC (p < 0.001). These findings suggest that adding butyric acid confers antimicrobial and antioxidant activity and improves birds’ production efficiency, intestinal health, and metabolism. Butyric acid glycerides are an effective alternative to conventional growth promoters.